Konsep Desain Kawasan Pesisir Berbasis Budaya Lokal Aceh: Sinergi Aktivitas Nelayan, Ornamen Tradisional, dan Ruang Budaya - Qanitatul Isra Qamal; Muhammad Aljabir; Ristia Natashrah; Omri Syafrizal; Helmi H (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The coastal area of Pantai Jangka in Aceh is a region with strong natural and cultural potential, with the lifestyle of the local fishing communities serving as a key factor in defining the character of the area. However, coastal development has not been able to integrate Acehnese identity and the activities of the fishing communities into the spatial structure of the area. Local culture is not represented spatially or visually, while activities that frequently occur are often perceived as disturbances in coastal development. This study aims to develop a concept for the Pantai Jangka coastal area based on Acehnese local culture, integrating traditional ornaments, the lifestyle of the fishing communities, and Acehnese cultural elements. A qualitative descriptive approach through field observation and literature analysis was employed in this research. The findings indicate that the Pantai Jangka coastal area faces major issues, including overlapping land use, weak visual identity, and a lack of spatial culture that supports social activities. Based on these findings, a spatial planning concept is proposed, including zoning for fishing villages, culture-based public spaces, and the development of educational tourism and the local economy. This concept is expected to strengthen the area’s identity, improve the quality of coastal spaces, and promote community-based development among the fishing population.